Climatic disasters and distracted analysts - Han, Yuqi; Mao, Connie X.; Tan, Hongping; Zhang, Chi (Contemporary Accounting Research, 2024)
Abstract Using a sample of 30,270 forecasts by 2,280 analysts under a stacked difference‐in‐differences framework involving 22 major climatic disasters in the United States, we examine the effect of climatic disasters on information production by security analysts, who play a crucial role in the financial market as information intermediaries. We find that earnings forecasts by analysts who experienced a major climatic disaster become less accurate than those by unaffected analysts within 3 months after the disaster, due to distracted attention. Disaster‐zone analysts are more likely to allocate their attention to firms of greater importance or salience, and they tend to reiterate their previous forecasts to maintain the quantity and timeliness of their forecasts. Overall, we document the real impact of cognitive bias on financial professionals' performance.